The Impact of Information Sources and Access to Health Facilities on the Continuity of Contraceptive Use - Agushybana, Farid; Siramaneerat, Issara; Islakhiyah, Islakhiyah; Nisa, Rofifatun (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: The family planning program (Keluarga Berencana or KB) is one of the Indonesian government’s efforts to suppress population growth. The program focuses on contraceptive usage. However, in practice, the level of continuity of contraceptive use are still low. The purpose of this study is to analyze the effect of sources of information and access to health facilities on the continuity of contraceptive use.Method: This quantitative study with a cross-sectional design had 1,195 respondents with an age range of <20 years to >35 years. Data were collected through structured interviews and questionnaires. Univariate data analysis was conducted with frequency distribution; bivariate data analysis utilized crosstabs, and the multivariate analysis used logistic regression.Results: The continuity of contraceptive use was 91.9% among respondents who received information about the family planning program, either orally, on mass media, or electronically, and it was 82.8% among respondents who accessed family planning services. This study found that factors that influence the continuity of contraceptive use were sources of electronic media information (OR = 0.6633; 95% CI = 0.4852 – 0.9067; p = 0.010) and access to family planning services (OR = 2.677; 95% CI = 1.652 – 4.337; p = 0.001). These findings suggest that the sources of information and access to health facilities affect the continuity of contraceptive use.